Minimal mask immobilization with optical surface guidance for head and neck radiotherapy - Zhao, Bo; Maquilan, Genevieve; Jiang, Steve; Schwartz, David L. (Journal of applied clinical medical physics, 2018)
Purpose Full face and neck thermoplastic masks provide standard‐of‐care immobilization for patients receiving H&N IMRT. However, these masks are uncomfortable and increase skin dose. The purpose of this pilot trial was to investigate the feasibility and setup accuracy of minimal face and neck mask immobilization with optical surface guidance. Methods Twenty patients enrolled onto this IRB‐approved protocol. Patients were immobilized with masks securing only forehead and chin. Shoulder movement was restricted by either moldable cushion or hand held strap retractors. Positional information, including isocenter location and CT skin contours, were imported to a commercial surface image guidance system. Patients typically received standard‐of‐care IMRT to 60–70 Gy in 30–33 fractions. Patients were first set up to surface markings with optical image guidance referenced to regions of interest (ROIs) on simulation CT images. Positioning was confirmed by in‐room CBCT. Following six‐dimensional robotic couch correction, a new optical real‐time surface image was acquired to track intrafraction motion and to serve as a reference surface for setup at the next treatment fraction. Therapists manually recorded total treatment time as well as couch shifts based on kV imaging. Intrafractional ROI motion tracking was automatically recorded by the optical image guidance system. Patient comfort was assessed by self‐administered surveys. Results Setup error was measured as six‐dimensional shifts (vertical/longitudinal/lateral/rotation/pitch/roll). Mean error values were −0.51 ± 2.42 mm, −0.49 ± 3.30 mm, 0.23 ± 2.58 mm, −0.15 ± 1.01o, −0.02 ± 1.19o, and 0.06 ± 1.08o, respectively. Average treatment time was 21.6 ± 8.4 mins). Subjective comfort during surface‐guided treatment was confirmed on patient surveys. Conclusion These pilot results confirm feasibility of minimal mask immobilization combined with commercially available optical image guidance. Patient acceptance of minimal mask immobilization has been encouraging. Follow‐up validation, with direct comparison to standard mask immobilization, appears warranted.